General anesthetic conditions induce network synchrony and disrupt sensory processing in the cortex - Lissek, Thomas; Obenhaus, Horst-Andreas; Ditzel, Désirée A. W.; Nagai, Takeharu; Miyawaki, Atsushi; Sprengel, Rolf; Hasan, Mazahir (Frontiers in cellular neuroscience, 2016)
General anesthetics are commonly used in animal models to study how sensory signals are represented in the brain. Here, we used two-photon (2P) calcium activity imaging with cellular resolution to investigate how neuronal activity in layer 2/3 of the mouse barrel cortex is modified under the influence of different concentrations of chemically distinct general anesthetics. Our results show that a high isoflurane dose induces synchrony in local neuronal networks and these cortical activity patterns closely resemble those observed in EEG recordings under deep anesthesia. Moreover, ketamine and urethane also induced similar activity patterns. While investigating the effects of deep isoflurane anesthesia on whisker and auditory evoked responses in the barrel cortex, we found that dedicated spatial regions for sensory signal processing become disrupted. We propose that our isoflurane-2P imaging paradigm can serve as an attractive model system to dissect cellular and molecular mechanisms that induce the anesthetic state, and it might also provide important insight into sleep-like brain states and consciousness.
Gesehen am 28.05.2020